Efficient in planta production of amidated antimicrobial peptides that are active against drug-resistant ESKAPE pathogens - Chaudhary, Shahid; Ali, Zahir; Tehseen, Muhammad; Haney, Evan F.; Pantoja-Angles, Aarón; Alshehri, Salwa; Wang, Tiannyu; Clancy, Gerard J.; Ayach, Maya; Hauser, Charlotte; Hong, Pei-Ying; Hamdan, Samir M.; et al. (Nature communications, 2023)
Antimicrobial peptides (AMPs) are promising next-generation antibiotics that can be used to combat drug-resistant pathogens. However, the high cost involved in AMP synthesis and their short plasma half-life render their clinical translation a challenge. To address these shortcomings, we report efficient production of bioactive amidated AMPs by transient expression of glycine-extended AMPs in Nicotiana benthamiana line expressing the mammalian enzyme peptidylglycine α-amidating mono-oxygenase (PAM). Cationic AMPs accumulate to substantial levels in PAM transgenic plants compare to nontransgenic N. benthamiana . Moreover, AMPs purified from plants exhibit robust killing activity against six highly virulent and antibiotic resistant ESKAPE pathogens, prevent their biofilm formation, analogous to their synthetic counterparts and synergize with antibiotics. We also perform a base case techno-economic analysis of our platform, demonstrating the potential economic advantages and scalability for industrial use. Taken together, our experimental data and techno-economic analysis demonstrate the potential use of plant chassis for large-scale production of clinical-grade AMPs. Antimicrobial peptides (AMPs) are next-generation antibiotics that can be used to combat drugresistant pathogens. Here, the authors report efficient production of bioactive amidated AMPs by transient expression in Nicotiana benthamiana line expressing the mammalian enzyme peptidylglycine α-amidating mono-oxygenase.